Primary school pupils’ misconceptions of the human respiratory system in primary school students: from identification to deconstruction - Silva, Marina (2020)
This study involved 38 students from the 6th year of schooling attending a state school in Lisbon in which the Science syllabus is centered on the study of human body systems. Its purpose was to determine: (i) whether the students possessed any of the misconceptions related to the human respiratory system referenced in other studies (e.g. air enters and leaves our bodies with no function, air tubes connect the lungs to the heart, the air exhaled is rich in carbon dioxide and poor in oxygen); (ii) whether a learning design focused on the deconstruction of these misconceptions would be effective to the conceptual change of these pupils. To this end, the experimental group (class A) experienced a learning design expressly conceived for the deconstruction of the misconceptions related to the human respiratory system, while the control group (class B) experienced a traditional approach with interactive lectures and use of the school textbook. The data were collected through a questionnaire administered in two stages (pre and post-test) and a t-test was used to compare the means obtained by the two groups in the pre-test and to verify the gains of each class between the pre and the post-test. After analysis of the results of the pre-test, it was found that the students of the two groups had several misconceptions of the human respiratory system. The experimental group had more significant gains, although the students in both groups reduced their misconceptions. Both results support the idea that formal education, if provided with well-structured activities, can contribute to the conceptual restructuring of the students’ mind, albeit with a different rate of success. Finally, the present study also helps to confirm the universality of certain misconceptions.